Vibration effects on convection in a rotating fluid saturated porous layer distant from the axis of rotation. (October 2019) - Govender, S.
Abstract: An analytical investigation for the onset of convection in a vertical saturated porous layer distant from the axis of rotation is presented when vibration is present. A linear stability analysis is used to determine the convection threshold in terms of the critical Rayleigh number for variation within the porous layer and for the offset distance from the axis of rotation. The results indicate that the presence of vibration stabilizes the convection across the range of offset distances. The effect of decreasing the offset distance (from very large to almost zero) serves to destabilize the critical Rayleigh number due to offset distance and to stabilize the Rayleigh number for variations within the porous layer.